Progress and the Lack of Progress in Addressing Infant Health and Infant Health Inequalities in Ireland during the 20th Century - McGovern, Mark E. (Statistical and Social Inquiry Society of Ireland, 2016)
There is a growing literature which documents the importance of early life environment for outcomes across the life cycle. Research, including studies based on Irish data, demonstrates that those who experience better childhood conditions go on to be wealthier and healthier adults. Therefore, inequalities at birth and in childhood shape inequality in wellbeing in later life, and the historical evolution of the mortality and morbidity of children born in Ireland is important for understanding the current status of the Irish population. In this paper, I describe these patterns by reviewing the existing literature on infant health in Ireland over the course of the 20th century. Up to the 1950s, infant mortality in Ireland (both North and South) was substantially higher than in other developed countries, with a large penalty for those born in urban areas. The subsequent reduction in this penalty, and the sustained decline in infant death rates, occurred later than would be expected from the experience in other contexts. Using records from the Rotunda Lying-in Hospital in Dublin, I discuss sources of disparities in stillbirth in the early 1900s. Despite impressive improvements in death rates since that time, a comparison with those born at the end of the century reveals that Irish children continue to be born unequal. Evidence from studies which track people across the life course, for example research on the returns to birthweight, suggests that the economic cost of this early life inequality is substantial.
Read before the Society, 3 March 2016 (Barrington Lecture 2015/16)
Keywords: infant mortality; early life conditions; inequality; 314.15